2022
DOI: 10.1093/rheumatology/keac587
|View full text |Cite
|
Sign up to set email alerts
|

Biologics with or without methotrexate in treatment of polyarticular juvenile idiopathic arthritis: effectiveness, safety and drug survival

Abstract: Objective To investigate the impact of additionally given methotrexate (MTX) on biologic treatment of polyarticular juvenile idiopathic arthritis (JIA) in terms of effectiveness, safety and drug survival. Methods Patients suffering from polyarticular JIA and treated with either monotherapy with a first biologic or a combination of a biologic and MTX were selected from the BIKER registry. The tumour necrosis factor α-inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…In previous studies, in contrast with anti-TNFi, no improvement in outcome has been observed by combining TCZ with cDMARD. So, TCZ was identified as being highly effective as a monotherapy (6,23). In this study, TCZ mono-and combination therapies were most commonly preferred for the treatment of RF-polyarticular JIA and JIAassociated uveitis, and were effective and well tolerated.…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, in contrast with anti-TNFi, no improvement in outcome has been observed by combining TCZ with cDMARD. So, TCZ was identified as being highly effective as a monotherapy (6,23). In this study, TCZ mono-and combination therapies were most commonly preferred for the treatment of RF-polyarticular JIA and JIAassociated uveitis, and were effective and well tolerated.…”
Section: Discussionmentioning
confidence: 92%